The Relationship of Knowledge and Family Attitudes towards Household Waste Management in Pakkat Toruan, Doloksanggul District, Humbang Hasundutan Regency in 2024 - Sihite, Helprida; Simamora, Debora Natalia (Mandalika Institute, 2024)
Indonesia is the fourth largest country in the world that faces environmental sanitation problems, especially waste management. Unmanaged household waste can have an impact on the health of the family. Household Waste Management is the right action to overcome problems related to waste. The purpose of the research is to find out the Relationship of Knowledge and Attitudes of the Pakkat Toruan Family in Household Waste Management. This type of research is a descriptive analytical crosssectional design. It will be held in March-May 2024 at Pakkat Toruan, Doloksanggul District. The population is 138 families in Pakkat Toruan. Sampling techniques were accidental sampling and chi-square test. The results of the study using the chi-square test showed that there was a relationship of knowledge to household waste management, the results of the chi-square test (α=0.05) and df =2 were obtained X2 count (6.124) > x2 table (5.991), there was a relationship between attitudes towards household waste management obtained from the Chi-Square Test df = 1 obtained X2 count (3.882) > chi-square (3.841). For the community, the importance of increasing family participation and skills in Household Waste Management as well as balanced funding and public understanding related to PHBS is the optimal Household Waste Management for improving the degree of family health status. It is hoped that the local government needs to cooperate with families to increase socialization, especially handling household waste.